(untitled) (Research, Society and Development, 2022)
The energy sector in Mozambique faces huge challenges that include low generation capacity and efficiency, affordability, unstable and unreliable energy supplies, low access rates, amongst others. The situation is being worsened by high environmental, social vulnerability and extreme events influenced by climate catastrophes. With the demand of energy consistently on the rise, there is critical need to address policy, investment, market and technical barriers to energy sector development. Mozambican government has made tremendous effort in developing electricity sector regulatory frameworks. However, progress has been uneven across the country. Thus, the aim of the study was to identify potential opportunities to promote the introduction of new distributed generation policies and technologies from renewable sources in Mozambique by analyzing technological and regulatory components of the energy sector in Argentina, Italy and Mexico. Methodologically, the study uses a comprehensive literature review, several national policy frameworks and statistical data from various official sources, with public policy and sectoral performance, as well as organizational and regulatory changes in consideration. Understanding national electricity market regulations and strategies, it will enable to gain a sense of perspective of the major determinants of the sector performance, and both the potential for and constraints on regulatory reform. It was observed that for achieving efficiency in energy provision, fair pricing, equality of access and environmental sustainability, it is important to strengthen the independence of the regulator.